KEBIJAKAN EKONOMI POLITIK CINA DI KAWASAN MELALUI CHIANG MAI INITIATIVE MULTILATERALIZATION (CMIM) DAN CINA-ASEAN BILATERAL SWAP AGREEMENTS - , NURFADHILAH AFANDY ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The regionâs economies were confronted with serious problems during the Asian Financial crisis 1997/1998 and the impact of global crisis 2008/2009, these phenomena depict the high susceptibility of the countries in the region to the financial instability. The high dependence of one countryâs financial and monetary relations with the other broadens the importance of the regional financial safety nets. The ASEAN+3 countries, including China, Japan, and then South Korea agreed to establish the Chiang Mai Initiativein 2000 and its multilateralization in 2009. CMIM is functioned as the regional mechanism with liquidity provision and macroeconomic surveillance feature for the member countriesâ economies. CMIM liquidity is based on the countryâs contribution, and put China and Japan as the biggest contributor to the regime. However, since its establishment the CMIMâs liquidity has never been activated, as the member country preferred the other mechanism outside the region in times of crisis, as showed during 2008/2009 global crisis. This emphasizes the current challenges faced as CMIM liquidity perceived insufficient to meet the member countriesâ needs as well as IMFâs high involvement in each of CMIM swap disbursement. Hence, this research examines the significance of Chinaâs involvement in the regime as the largest contributor, which will answer how China maintain its engagement and its substantial commitment to strengthen the CMIM, more importantly, Chinaâs Bilateral Swap Agreements in the region have also been perceived could contest the CMIM effectiveness, as Chinaâs BSAs which actively pursued in the region has similar use to the CMIM liquidity objective.